Medical Therapy of Steroid-Resistant Crohn's Disease - Bruce E Sands (Canadian Journal of Gastroenterology)
Glucocorticosteroids are commonly used in the treatment of moderate to severe Crohn’s disease and are effective for the short term amelioration of symptoms. However, not all patients respond to corticosteroid therapy. Approximately 20% of patients fail to respond to initial treatment with steroids, while 36% of patients may be considered steroid dependent. Sharp distinctions between steroid-dependent and steroid-resistant populations are difficult to draw because steroid responsiveness is often dose dependent. Clearer distinctions may be drawn between those who fail to respond to initial treatment with corticosteroids and those who have secondary failure later in the course of their disease on repeated treatment. Effective therapies for steroid-resistant Crohn’s disease include azathioprine and 6-mercaptopurine, methotrexate, cyclosporine and infliximab. Limited data are available on the use of tacrolimus, mycophenolate mofetil and thalidomide. Steroid-resistant Crohn’s disease, while involving a small minority of patients, continues to present a difficult therapeutic challenge.